Atrial fibrillation and arterial hypertension. (February 2018) - Kallistratos, M.S; Poulimenos, L.E.; Manolis, A.J.
Graphical abstract: Abstract: Atrial fibrillation (AF) and arterial hypertension frequently coexist, not only because arterial hypertension increases the incidence of new onset of atrial fibrillation, but also because those two entities share common risk factors and conditions that increase the incidence of both. Thus, in our daily clinical practice we will often have to manage and treat those patients. In order to assess and treat these patients, proper blood pressure (BP) measurement as well as detection of atrial fibrillation is mandatory. The use of oscillometric devices for home and ambulatory blood pressure measurements may accurately measure systolic but not diastolic blood pressure levels. Current guidelines suggest to palpate the pulse and perform an electrocardiogram (ECG) as well as a long-term ECG monitoring in order to detect AF. However there is evidence that: the use of oscillometric BP device with a specific algorithm for the detection of AF as well as the interrogation of a permanent pacemaker may further help physicians to reveal periods of AF. Finnaly, although guidelines suggests the use of specific drugs in order to treat arterial hypertension in AF patients, the main goal is BP control per se. In this review, we are going to summarize the diagnostic work up of these patients namely the proper arterial blood pressure measurement, the detection of atrial fibrillation as well as the treatment of these patients based on the latest data of the literature.